Helicobacter pylori as a trigger and aggravating factor in rheumatoid arthritis and other rheumatic diseases - A. O. Plakhova; E. S. Nikitina; V. N. Sorotskaya; A. E. Karateev (Современная ревматология, 2017)
Helicobacter pylori is the most common human infection. H. pylori is known to cause chronic gastritis and gastric and duodenal ulcers. However, the H. pylori-host interaction is not confined to the gastric mucosa, the mechanism responsible for the adaptation of this bacterium to the living conditions in the human body, can cause systemic immune imbalance, provoking various autoimmune reactions. The paper considers the investigations demonstrating the possible role of H. pylori as a trigger or aggravating factor in rheumatic diseases, such as rheumatoid arthritis (RA), Sjögren's syndrome and disease, systemic lupus erythematosus, and progressive systemic sclerosis. The relationship between H. pylori and autoimmune diseases is confirmed by the higher frequency of more aggressive strains of this microorganism in rheumatic diseases. There are also clinical trials showing the positive impact of H. pylori eradication on RA activity.